Effectiveness of Islamic Group Spiritual Therapy on Happiness and Reduction of Loneliness Among Women Visiting Counseling Centers in Bushehr - Mohannaee, Setareh; Poorgholamy, Farzad; Mousavi Shoorgoli, Seyyedeh Sahar; Raeissaadi , Raeis hasan (Psychology of Woman Journal, 2025)
Objective: This study aimed to assess the effectiveness of Islamic group spiritual therapy on happiness and the reduction of loneliness among women visiting counseling centers in Bushehr in the first half of 2024.Methods and Materials: The study employed a quasi-experimental design with a pre-test and post-test approach, including a control group. The statistical population consisted of women visiting counseling centers in Bushehr. A sample of 30 women was selected using voluntary sampling and randomly assigned to either the experimental or control group. The Argyle, Martin, and Crossland (1989) Happiness Questionnaire and the Russell, Peplau, and Cutrona (1980) Loneliness Scale were administered to both groups. For the experimental group, a group spiritual therapy program based on the therapeutic framework by Dasht Bozgi and colleagues (2016) was conducted in 8 sessions, each lasting 90 minutes.Findings: The results revealed that Islamic group spiritual therapy had a significant effect on happiness and its components, including self-concept, life satisfaction, psychological readiness, cheerfulness, aesthetic sense, self-efficacy, and hopefulness, as well as on the reduction of loneliness (p < 0.05).Conclusion: Islamic group spiritual therapy can have a positive impact on enhancing happiness and reducing loneliness among women.